Studi Dampak Level Penetrasi Pembangkit Listrik Fotovoltaik pada Jaringan Distribusi - Septianissa Azzahra; Agus Yogianto; Ibnu Hajar (Energi & Kelistrikan, 2019)
Recently distribution network have connected with power plant unit also with photovoltaic power plant. Therefore voltage profile of distribution grid not any more distance from source there is voltage drop but connected with photovoltaic power plant would be increase grid voltage in this connected point also in the grid line. In this study, the distribution grid with connected with photovoltaic power plant is modelled. By using through MATHLAB / SIMULINK, modeling and simulation can be done ondistribution grid with two point connected to the photovoltaic power plant. From the simulation and analysis obtained, that power injection to grid by photovoltaic power plant can affect voltage grid condition, but not affect grid frequency relatively. The grid voltage will increase if there is power injection to the connected point in grid. Increase the power penetration to the grid would be increase the rise voltage in the grid. The constraint in this case, that power penetration must be considered the condition of quality voltage because any trend for voltage wave become distorted.